Development of a Molecular Signature to Monitor Pharmacodynamic Responses Mediated by In Vivo Administration of Glucocorticoids. Issue 8 (12th July 2018) - Hu, Yanhua; Carman, Julie A.; Holloway, Deborah; Kansal, Selena; Fan, Li; Goldstine, Christine; Lee, Deborah; Somerville, John E.; Latek, Robert; Townsend, Robert; Johnsen, Alyssa; Connolly, Sean; et al.
Abstract : Objective: To develop an objective, readily measurable pharmacodynamic biomarker of glucocorticoid (GC) activity. Methods: Genes modulated by prednisolone were identified from in vitro studies using peripheral blood mononuclear cells from normal healthy volunteers. Using the criteria of a >2‐fold change relative to vehicle controls and an adjusted P value cutoff of less than 0.05, 64 up‐regulated and 18 down‐regulated genes were identified. A composite score of the up‐regulated genes was generated using a single‐sample gene set enrichment analysis algorithm. Results: GC gene signature expression was significantly elevated in peripheral blood leukocytes from normal healthy volunteers following oral administration of prednisolone. Expression of the signature increased in a dose‐dependent manner, peaked at 4 hours postadministration, and returned to baseline levels by 48 hours after dosing. Lower expression was detected in normal healthy volunteers who received a partial GC receptor agonist, which is consistent with the reduced transactivation potential of this compound. In cohorts of patients with systemic lupus erythematosus and patients with rheumatoid arthritis, expression of the GC signature was negatively correlated with the percentages of peripheral blood lymphocytes and positively correlated with peripheral blood neutrophil counts, which is consistent with the known biology of the GC receptor. Expression of the signature largely agreed with reported GC use in these populations, although there was significant interpatient variability within the dose cohorts. Conclusion: The GC gene signature identified in this study represents a pharmacodynamic marker of GC exposure.